Celestine Bassey and Oshita Oshita (eds). 2007. Conflict Resolution, Identity Crisis and Development in Africa. Lagos: Malthouse Press Limited. 275pp. - Egbe, Olawari D.J (Advances in Social Sciences Research Journal, 2015)
Celestine Bassey and Oshita Oshita (eds). 2007. Conflict Resolution, Identity Crisis and Development in Africa. Lagos: Malthouse Press Limited. 275pp.